Sistem Informasi Keamanan Kunci Pintu Pintar Berbasis Internet of Things Notifikasi Real-Time Berbasis WhatsApp - Kaleb Suy; Sufajar Butsianto; Supriyanto (Bulletin of Computer Science Research, 2025)
Security remains a primary concern in domestic and marketable structures, especially as conventional door cinches come decreasingly vulnerable to duplication and forced access. This study presents the design and perpetration of a smart door lock security system grounded on Internet of Things and Radio frequence Identification technologies. The main ideal is to give a real- time, ever controlled locking medium integrated with a mobile- grounded messaging platform. The development process adopts the nimble methodology, which promotes inflexibility, responsiveness to stoner feedback, and rapid-fire replication in software and tackle integration. The tackle armature utilizes ESP32 and Arduino Nano microcontrollers to manage essential factors, including RFID compendiums, relays, buzzers, solenoid cinches, LED and LCD as display module. On the software side, the system incorporates a pall connected messaging operation to deliver real- time announcements to druggies, including cautions for unauthorized access attempts, successful entries, and low battery warnings. Data communication between the microcontrollers is enforced via periodical protocol, while the commerce with the messaging service is established using the HyperText Transfer Protocol. Testing involved colorful scripts including valid access, unrecorded card attempts, and remote commands. The testing scenario uses three RFID cards and a WhatsApp chatbot, with one card as the master and the other two as access cards, with each card undergoing three trials. Results demonstrate a high success rate in card discovery and command prosecution with an average system response time below one second. The system also allows druggies to register and remove access cards via a master card medium, which enhances usability and control. This exploration contributes a low- cost, customizable, and effective security result suitable for smart homes, boarding houses, and small- scale marketable parcels. It shows the feasibility of integrating open- source microcontrollers with everyday messaging tools to achieve effective, real- time home security. The proposed system provides a foundation for unborn exploration in combining internet grounded control systems with biometric detectors or machine literacy grounded access analytics such as developing a separate mobile application so that it does not use third-party applications, allowing users to obtain more accurate feedback through door leaf detector sensors.